Land cover change and its associated impacts on landscape fragmentation and flood exposure in Quinali a watershed, Albay, the Philippines - Agudo, Gifford Jay L. (Philippine Journal of Science, 2025)
Detrimental land cover conversion has emerged as a pressing issue in the Quinali A Watershed, Albay, the Philippines. However, there has been a lack of monitoring regarding the change and its repercussions. Establishing baseline information is imperative to enable informed decisions and policies toward sustainable development. Landsat images were used to analyze the land cover changes in Quinali A Watershed from 1990–2020. Two-dimensional flood models and landscape metrics derived from FRAGSTATS were employed to assess the impacts of land cover change on flood exposure and landscape fragmentation. Results revealed that cropland, artificial surfaces, submerged vegetation, and inland water increased since 1990, but at the expense of forest, brushland, and barrenland. Generally, flooding occurs in areas of topographic lows of the watershed. The expansion of artificial surfaces took place in flood-prone areas, nearly doubling the flood exposure rates recorded in 1990. Despite cropland expansion, it decreased in the low-lying areas of the watershed, resulting in reduced exposure to flooding. The annual rate of change indicates substantial increases of 2.77 and 0.79% in NP for artificial surfaces and barren land, respectively, with ED increasing by 2.73 and 0.74%. AWM increased by 1.62% in non-forest areas, whereas forest areas showed an increase of 0.65%. Although the PAFRAC decreased by 0.02%, it maintained a high value of 1.53 in 1990 and 1.52 in 2020, indicating low stability of the land cover structure within the watershed landscape. Continuous monitoring of these changes is imperative to recommend science based policies that can regulate resource utilization in Quinali A Watershed.